Achieving green and deep-blue perovskite LEDs by dimensional control using various ammonium bromides with CsPbBr-3. (September 2021) - Kang, S.; Park, S.; Park, S.; Kwon, H.; Lee, J.; Hong, K.-H.; Pu, Y.-J.; Park, J.
Abstract: In this study, green and blue perovskite light-emitting diodes (PeLEDs) were systematically investigated using various organic spacers of different molecular lengths to control the number of dimensions of the PeLED material. The primary perovskite used was CsPbBr3, and the organic spacers tested were aniline hydrobromide (AnBr), benzylamine hydrobromide (BABr), phenylethylamine hydrobromide (PEABr), phenylpropylamine hydrobromide (PPABr), and phenylbutylamine hydrobromide (PBABr). By specifically testing different amounts of each spacer, green to blue PeLEDs were prepared and analyzed using XRD and SEM. The best optical and electrical performances were obtained with PEABr as the organic spacer. Using 0.4 mol of PEABr for 1 mol of CsPbBr3 yielded a green electroluminescence (EL) emission with a CIE of (0.078, 0.745), a maximum current efficiency of 43.9 cd/A, and an EQE of 8.67%, and using 1.6 mol of PEABr per mole of CsPbBr3 yielded a blue EL emission with a CIE of (0.151, 0.084), a maximum current efficiency of 0.87 cd/A, and an EQE of 0.39%. Graphical abstract: Image 1 Highlights: Optimization of low-dimensional perovskite formation through various organic spacer lengths. Implementation of green to deep-blue perovskite LEDs with an optimized organic spacer (PEABr). Green emission showed a maximum EL at a wavelength of 513 nm, FWHM of 20 nm, CIE of (0.078, 0.745), maximum efficiency of 43.9 cd/A, and EQE of 8.67%.